Heartware as a driver for campus sustainability: Insights from an action-oriented exploratory case study - Mohamad, Zeeda Fatimah; Abd Kadir, Siti Norasiah; Nasaruddin, Affan; Sakai, Nobumitsu; Mohamed Zuki, Fathiah; Hussein, Hazreena; Sulaiman, Abdul Halim; Mohd Salleh, Mohammad Shahrul Amin (Elsevier, 2018)
Literature on campus sustainability transitions is mainly focused on the hardware and software approaches, with less attention on the so-called ‘heartware’ approach. Heartware refers to the internal and voluntary motivation of the campus community itself to establish long-term collaboration and collective efforts for sustainability. The paper addresses this gap through an action-oriented exploratory case study research in applying the heartware approach for a long-term water conservation initiative at the University of Malaya campus in Malaysia. The case study research employed a triangulation of five types of data sources (documentation, archival records, direct observation, physical artifacts and participant observation) and two analysis techniques (iterative explanation building and time-series analysis). The case study demonstrated that the heartware approach can be an essential driver for campus sustainability, with suggestions on three ways it can be exercised: (1) Community-shared values that can inspire collective and voluntary action on campus; (2) Role of volunteers within the campus community, at various levels of power, in galvanizing efforts; (3) Heartware driven adaptive governance - where the campus community is able to self-maneuver in mediating conflicts that can possibly block long term action. The paper concludes that there can be aspirational ways to view our campuses: as a living community with concerned citizens, rather than just a complex organization to be managed. This might open up more rooted solutions for campus sustainability than what is currently available.